2021
DOI: 10.32815/jibeka.v15i2.350
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Market Orientation, Entrepreneurial Orientation Terhadap Kinerja Perusahaan Dengan Mediasi Absorptive Capacity

Abstract: Tujuan penelitian ini adalah untuk menganalisis pengaruh market orientation, entrepreneurial orientation terhadap kinerja perusahaan melaui absorptive capacity. Penelitian ini dilakukan pada pada Hotel Non Bintang di Kepulauan Riau. Metode analisis data yang digunakan dalam penelitian ini adalah Partial Least Square Structural Equation Market (PLS-SEM) dengan bantuan program SmartPLS Versi 3. Sampel penelitian ini adalah manajer/direktur hotel non bintang di Kepulauan Riau. Hasil penelitian ini adalah mengungk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
1
4
1
Order By: Relevance
“…The results of this study are in line with the results of research conducted by [9]; [14]; [17]; [15] which explain that entrepreneurial orientation has a positive and significant effect on MSME performance. However, the results of this study are not in line with the research of [18]; [20] who found that entrepreneurial orientation has no significant effect on business performance. Entrepreneurial orientation has an influence in improving the performance of MSMEs.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of this study are in line with the results of research conducted by [9]; [14]; [17]; [15] which explain that entrepreneurial orientation has a positive and significant effect on MSME performance. However, the results of this study are not in line with the research of [18]; [20] who found that entrepreneurial orientation has no significant effect on business performance. Entrepreneurial orientation has an influence in improving the performance of MSMEs.…”
Section: Resultscontrasting
confidence: 99%
“…[15] in their research on 226 MSME actors in Sri Lanka explained that absorptive capacity has a positive and significant effect on business performance. Then, [20] in his research on non-star hotel entrepreneurs in Riau Islands stated that there was a positive and significant effect of absorptive capacity on business performance. Furthermore, the results of research by [17] on 218 family business owners in Spain revealed that absorptive capacity has a positive and significant effect on business performance.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor that can affect performance is Entrepreneurial orientation. Entrepreneurial orientation according to Purwianti (2021) the willingness of organizations to find and accept new opportunities and subsequent changes to implement them as a result. Companies can use Entrepreneurial orientation in addition to using market orientation to achieve sustainable competitive advantage in an ever-changing business environment (Purwianti, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Entrepreneurial orientation according to Purwianti (2021) the willingness of organizations to find and accept new opportunities and subsequent changes to implement them as a result. Companies can use Entrepreneurial orientation in addition to using market orientation to achieve sustainable competitive advantage in an ever-changing business environment (Purwianti, 2021). Permana (2018) states that entrepreneurial orientation is better if measured by combining these three dimensions, pro-active (pursuing new opportunities to compete with competitors), innovative (innovating and developing a business to gain a competitive advantage) and risk taking (taking risks related to a business that is being run) (Melati et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation